Identifikasi tumbuhan lumut (Bryophyta) di Kawasan Hutan Topidi Kabupaten Gowa - Irawati, Irawati; Rustam, Aswar; Nurindah, Nurindah (Filogeni: Jurnal Mahasiswa Biologi, 2023)
Indonesia is located between mainland Asia and Australia which is an archipelago spread out in the world with no less than 17,500 islands with an area of ​​4500 km2. It has a tropical climate that causes Indonesia to have a high level of biodiversity, such as the islands located along the equator. Of the 40% thousand types of flora that grow in the world, 30 thousand of them grow in Indonesia. About 26% have been cultivated and the remaining 74% are still wild in the forest. The purpose of this study was to determine the types of mosses that exist in the Topidi forest area. The types of mosses were identified using the PlanNet application. The research was conducted using an exploratory survey method, which was carried out by observing directly the moss plants in the field. The results showed that in the topidi forest area, five types of mosses were found, including Fissidens atrovidis moss, Philonotis hastata moss, Hyophila apiculata moss, Rhynchostegiella manadensis moss and Barbula indica moss.